Answer:
h is the horizontal shift
Step-by-step explanation:
y = a(x – h)^2 + k
This is the equation for a parabola in vertex form
The vertex is ( h,k) and it is shifted from (0,0)
h is the horizontal shift and k is the vertical shift
Answer:
-226,981
Step-by-step explanation:
This is how you do it.
First, you do 3-2 which is 1.
Then, you do 3-4 to the 3rd power which is -61.
After, you do 1*-61 because there are parenthesis, which equals -61.
Then, you do -61, which is the total of everything in parenthesis, and do it times the power of 3 to get -226,981.
Hope it helps!!^_^
Answer:
A) 11/36
Step-by-step explanation:
x + 4/9 = 3/4
get a common denominator of 36 (4*9 = 36)
x + 4/9 * 4/4 = 3/4 * 9/9
x + 16/36 = 27/36
subtract 16/36 from each side
x + 16/36 - 16/36 = 27/36 -16/36
x = (27-16)/36
x = 11/ 36
Answer:
Step-by-step explanation:
From the question we are told that:
Length
Top length
Height
Rate
Water rise
Generally the equation for Velocity is mathematically given by
Therefore
Where
Therefore